Ecology - religion teaching programme for the III class of preparatory school - Łukomski, Julisław (Studia Ecologiae et Bioethicae, 2007)
The article presents analysises of the following issues from the ecological programme for the III class of preparatory school: human and nature in the light of christology, the elevation of human and universe by the Incarnation, Christss cross points the solidarity of God with human and whole nature, peace with God, peace with every creature, rationality of the nature tells about Creator s idea, crisis of moral values finds expression in degradation of natural environment, urgent need of solidarity.